Innovations and Challenges in Reducing Maternal Mortality in Tamil Nadu, India (Journal of Health, Population and Nutrition, 2009)
Although India has made slow progress in reducing maternal mortality, progress in Tamil Nadu has been rapid. This case study documents how Tamil Nadu has taken initiatives to improve maternal health services leading to reduction in maternal morality from 380 in 1993 to 90 in 2007. Various initiatives include establishment of maternal death registration and audit, establishment and certification of comprehensive emergency obstetric and newborn-care centres, 24-hour x 7-day delivery services through posting of three staff nurses at the primary health centre level, and attracting medical officers to rural areas through incentives in terms of reserved seats in postgraduate studies and others. This is supported by the better management capacity at the state and district levels through dedicated public-health officers. Despite substantial progress, there is some scope for further improvement of quality of infrastructure and services. The paper draws out lessons for other states and countries in the region. Key words: Maternal health; Maternal mortality; Obstetric care; Verbal autopsy; India doi: 10.3329/jhpn.v27i2.3364 J Health Popul Nutr 2009 April;27(2):202-219